Diabetes and the nervous system - Zochodne, Douglas W.; Malik, Rayaz A. (Handbook of clinical neurology ;, 2014)
This is a unique compilation, by experts worldwide, addressing how diabetes impacts the nervous system. For example, diabetic polyneuropathy, a disorder more common than MS, Parkinson's disease, and ALS combined, is a major source of disability to diabetic persons worldwide. This book addresses diabetic polyneuropathy and how diabetes alters other parts of the nervous system. * Offers a unique emphasis on the neurological manifestations of diabetes * Provides thorough coverage of the clinical, experimental, mechanistic, therapeutic, peripheral, and central aspects of diabetic neuropathy.- Resumé vydavatel